The Operational Efficiency of Public Higher Vocational Schools in the Lubelskie Voivodeship - Pyra Mariusz (Studia Ekonomiczne i Regionalne, 2020)
Subject and purpose of work: This paper aims to assess the operational efficiency of public higher vocational schools in the Lublin Region.